ANALISIS KESESUAIAN IMPLEMENTASI BUDAYA ORGANISASI 7 KARAKTER PADA MAHASISWA UNIVERSITAS DHYANA PURA - Yeyen Komalasari (Forum Manajemen STIMI Handayani Denpasar, 2019)
Organizational Culture is a very important factor in improving organizational effectiveness. Organizational culture can be a major competitive advantage instrument, when organizational culture supports organizational strategies and can answer or overcome environmental challenges quickly and accurately. The Organizational culture